Collection of Local Taxes in Insolvency Proceedings - Svobodová, Tereza (Central European Academy Law Review, 2025)
Local taxes take a very special place in the tax system of the Czech Republic. The process of administering local taxes is the same as for other taxes; however, their administration is not carried out by the tax authorities but by municipal authorities. They are the only part of municipal tax revenue that municipalities can directly influence the efficiency of collection. Today‘s economically challenging times have resulted in an increasing number of taxpayers being unable to pay their debts and ending up in insolvency. In the case of unpaid local taxes, municipalities become insolvent creditors, and the process of collecting local taxes enters the insolvency regime. This paper aims to identify the position of a municipality as a creditor in insolvency proceedings, which has tax debts against the debtor arising from unpaid local taxes, and find out whether municipalities actively use their right to enforce their claims in insolvency. The paper is based on the hypothesis that the municipality in the Czech Republic has a better position compared to other creditors because its tax debts have a public law character. First, the paper discusses the theoretical background, anchoring the position of the municipality in tax administration. Subsequently, the legal norms that regulate the issue of insolvency claims arising from unpaid taxes are analysed. The Czech approach is supplemented with case law conclusions to provide a comprehensive view of the issue. The results obtained from a questionnaire survey on whether municipalities use the examined tax collection option are presented. Based on the research, the hypothesis is refuted, and the findings are discussed and compared with continental and common law legislation.